(untitled) (UNED Research Journal, 2016)
Sustainable livestock production generates benefits for the environment, such as water capture, increased biodiversity and carbon dioxide capture. To measure these factors in a tropical setting, in 2007 we took three samples of a milk production system in Turrialba, Cartago, Costa Rica, in areas with permanent African Star grass cover (under grazing) and a secondary forest with 15 years of regeneration. We estimated carbon content in the microbial biomass, microbial activity (breathing technique), carbon usage profile (BIOLOG ECOPLATES®) and functional diversity of microorganisms (Shannon index). Biomass carbon in the pasture was 3,3 times higher than in the forest, but microbial activity was similar. Carbon use rate ranged from 22,22 to 85,19% in the pasture (higher in the forest: 29,63 to 92,59%). In both areas growth correlated with incubation time, but the forest had more biodiversity. Pasture areas are favored by carbon deposition to the rhizosphere, while the variety of vegetation in the forest allows greater functional diversity in the use of carbon substrates.